Case ‒ Uretero-internal iliac artery fistula presenting with multiple negative angiographic studies - Sarwal, Gautamn; Bidnur, Samir; Chedgy, Edmund C.P.; Kavanagh, Alex (Canadian Urological Association Journal, 2018)
We report a rare case of a patient presenting with visible, unexplained hematuria and share the diagnostic challenges faced in the setting of multiple angiographic studies that failed to demonstrate an uretero-internal iliac artery fistula. Uretero-arterial fistulas (UAF) are rare, but well-recognized, with increasingly common risk factors (Table 1).1 Due to its rarity, delay to diagnosis is common, when investigating recurrent hematuria with multiple negative investigations.1,2